2017
DOI: 10.7600/jpfsm.6.257
|View full text |Cite
|
Sign up to set email alerts
|

Postural stability and lower leg muscle activity during a diagonal single-leg landing differs in male collegiate soccer players with and without functional ankle instability

Abstract: The purpose of this study was to investigate postural stability and lower leg muscular activity in male collegiate soccer players with functional ankle instability (FAI), during a diagonal landing. Twenty-two male collegiate soccer players were divided into an FAI group (n = 11) and healthy control group (n = 11). Muscle reaction times for sudden ankle inversion were measured to evaluate neuromuscular control in the peroneus longus (PL), peroneus brevis (PB), tibialis anterior (TA), gastrocnemius lateral head … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Previous studies showed a decrease in ankle, knee, and hip EMG activity in people with CAI during functional balance tasks (single-leg balance with closed eyes, star test, and lateral hop) [ 7 , 22 ]. Similar to our results, one study showed lower MG EMG activity in individuals with CAI during single-leg stance when compared with healthy controls [ 31 ]. In contrast, one study reported greater MG EMG activity in the CAI group compared to the copers and healthy group [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies showed a decrease in ankle, knee, and hip EMG activity in people with CAI during functional balance tasks (single-leg balance with closed eyes, star test, and lateral hop) [ 7 , 22 ]. Similar to our results, one study showed lower MG EMG activity in individuals with CAI during single-leg stance when compared with healthy controls [ 31 ]. In contrast, one study reported greater MG EMG activity in the CAI group compared to the copers and healthy group [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…All muscle MVICs were measured prior to the testing protocol with the lower limb positioned at postures used in clinical manual muscle tests to achieve maximal contractions [5] . Each participant performed three 5-seconds attempts against manual resistance that was provided by the main investigator towards (i) inversion coupled with dorsal flexion and eversion coupled with plantar flexion of the ankle for TA and PB, respectively with each participant lying supine [ 6 , 7 ] and (ii) plantar flexion of the foot for GL and GM with each participant lying prone [6] . The EMG activity that corresponded to each muscle's MVIC was determined based on the average of the time interval between the 2nd and 4th seconds of each one of the three repetitions.…”
Section: Methods Detailsmentioning
confidence: 99%
“…Ankle sprain is very common among basketball, and soccer players because of the special nature of these sports, which involve movements such as rapid changes in direction, frequent jumping and landing, sudden stops, and collisions with opposing players during rebounding, defending, and tackling [ 1 , 2 ]. This type of injury accounts for 41.1% [ 3 ] and 14% [ 4 ] of the total number of injuries suffered by basketball and soccer players, respectively.…”
Section: Introductionmentioning
confidence: 99%